Emerging Role of Non-crystalline Electrolytes in Solid-State Battery Research - Grady, Zane A.; Wilkinson, Collin J.; Randall, Clive A.; Mauro, John C. (Frontiers in Energy Research, 2020)
As the need for new modalities of energy storage becomes increasingly important, all-solid-state secondary ion batteries seem poised to address a portion of tomorrow’s energy needs. The success of such batteries is contingent on the solid-state electrolyte (SSE) meeting a set of material demands, including high bulk and interfacial ionic conductivity, processability with electrodes, electrode interfacial stability, thermal stability, etc. The demanding criteria for an ideal SSE has translated into decades of research devoted to discovering new electrolytes and modifying their structure/processing to improve their properties. While much research has focused on the electrolyte properties of polycrystalline ceramics, non-crystalline materials (glasses, amorphous solids, and partially crystallized materials) have demonstrated unique advantages in processability, stability, tunability, etc. These non-crystalline electrolytes are also fundamentally interesting for their potential contributions toward understanding ionic conduction in the solid state. In this review, we first review a decade of advances in two distinct families of non-crystalline lithium-ion electrolytes: lithium thiophosphate and lithium phosphate oxynitride. In doing so, we demonstrate two pathways for non-crystalline electrolytes to address the barriers toward development of all-solid-state batteries, viz., interfacial stability and conduction. Finally, we conclude with some discussion of the development of fundamental models of ionic conduction in the non-crystalline state, including the ongoing debate between strong and weak electrolyte theories. Collectively, these discussions make a promising case for the role of non-crystalline electrolytes in the next generation of energy storage technology.